Mothers Caring for a Child at End of Life: A Systematic Review - Hafez, Shahad; Snethen, Julia; Ellis, Julie; Taani, Murad; Ngui, Emmanuel; Baothman, Abdullah A. (Journal Of Nursing Practice, 2021)
Background: A mother feels complete when she fulfills her role in protecting her child from harm.  If a child is diagnosed with a terminal illness and reaches End of Life (EOL), the mother’s life is affected negatively.  The mother is affected mentally, psychologically, and physically because her child is dying.Purpose: Explore the recent studies that focused on experiences of mothers caring for a child receiving End of Life Care (EOLC) at home or a healthcare facility.Methods: An electronic search was done in multiple databases, including the University of Wisconsin-Milwaukee Library, PsycINFO, PubMed, CINAHL, and Academic Search Complete. The included studies were published within the past five years, studies about EOL/ EOLC, hospice care, pediatric care, quantitative, qualitative, and mixed methods studies. Thematic synthesis following PRISMA guidelines.  Results: Four themes emerged from the thematic synthesis.  The main themes included decision making challenges, communication with healthcare professionals, parents’ support system, and grief. Parents were included in most studies. However, the number of mothers exceeded the number of fathers.  Some researchers mentioned that there was no difference between their participants (most participants were Caucasian).  Conclusion: There is limited information available about children and their family members’ experiences at EOL/ EOLC in Saudi Arabia as has been studied in other countries.  Based on this systematic review, more studies are needed related to children at EOL in Saudi Arabia.